2022
DOI: 10.31004/edukatif.v4i1.2113
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Stres Kerja, Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Guru

Abstract: Latar belakang penelitian rendahnya kierja guru di sekolah dilihat dari stres kerja, motivasi dan kepuasan kerja. Penelitian ini bertujuan untuk menjawab pertanyaan utama pengaruh stres kerja, motivasi kerja dan kepuasan kerja terhadap kinerja guru di Sekolah Dasar Negeri di Kecamatan Danau Sipin Kota Jambi. Penelitian ini menggunakan metode Kuantitif. Hasil penelitian menunjukan terdapat pengaruh langsung stres kerja terhadap kepuasan kerja dengan P value dibawah 0,05 dengan original sample sebesar (β) = 0,62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
2
4
0
6
Order By: Relevance
“…The results of the regression coefficients for the Teacher Motivation variable on Teacher Performance are 0.812 with a constanta value of 14,344, so it can be concluded that the simple linear regression equation is 𝑌 = 14.344 + 0,812𝑋 2 , it can be concluded that the Teacher Motivation variable has a positive effect on Teacher Performance at Kartika II-5 Elementary School Bandar Lampung. This is in line with the research results of Damayani et al (2020) and Sari et al (2022) which states that there is a significant influence of teacher work motivation on teacher performance. According to Sari et al (2021), The willingness to work will ultimately have an impact on the results of the work itself.…”
Section: Test Results Of Teacher Motivation Variables On Teacher Perf...supporting
confidence: 92%
“…The results of the regression coefficients for the Teacher Motivation variable on Teacher Performance are 0.812 with a constanta value of 14,344, so it can be concluded that the simple linear regression equation is 𝑌 = 14.344 + 0,812𝑋 2 , it can be concluded that the Teacher Motivation variable has a positive effect on Teacher Performance at Kartika II-5 Elementary School Bandar Lampung. This is in line with the research results of Damayani et al (2020) and Sari et al (2022) which states that there is a significant influence of teacher work motivation on teacher performance. According to Sari et al (2021), The willingness to work will ultimately have an impact on the results of the work itself.…”
Section: Test Results Of Teacher Motivation Variables On Teacher Perf...supporting
confidence: 92%
“…In that case, this motivates them to work harder to earn the same salary as men. (Sari et al, 2022) research studies teacher performance through three independent variables: work stress, motivation, and job satisfaction. It shows a direct effect of work stress on job satisfaction, an immediate impact of job stress on teacher performance, and a direct influence of work motivation on job satisfaction.…”
Section: Introduction *mentioning
confidence: 99%
“…Kinerja dikatakan sebagai hasil kerja dari seorang karyawan dalam menyelesaikan tugasnya sesuai dengan ketentuan yang telah ditetapkan oleh perusahaan, penilaian kinerja dapat dilakukan dengan dua cara yaitu kinerja kualitatif indikator pengukurnya adalah mutu dari hasil pekerjaan yang telah selesai dan kinerja kuantitatif merupakan hasil pekerjaan yang dapat diukur berdasarkan data atau angka (Antaiwan Bowo Pranogyo SE et al, 2022;Riyadi, 2022). Kinerja karyawan merupakan hal yang sangat penting bagi perusahaan dimana baik buruknya sebuah kinerja akan sangat mempengaruhi proses produksi barang atau penyampaian jasa (Fathoroni et al, 2020).…”
Section: Pendahuluanunclassified